Channel Controlled Foraminiferal Distribution off Bakkhali, West Bengal, India - Sachin Kumar Tripathi; Resmi S.; Satyendra Baraik; Debasis Sengupta; Amitava Lahiri (BULLETIN OF THE MARINE GEOLOGY, 2018)
Study area is situated 8 km south of the Bakkhali Island, West Bengal of India and its subaqueous environment influenced by the fluvial processes such as Hooghly River in west and its distributary like Muri Ganga in the centre and Saptamukhi River in the east. To understand the submarine behavior of these channels and associated meiobenthos, total of 28 sediment samples have been studied in detail. The study reveal that a total of fifteen species of recent benthic foraminifera belonging to 13 genera under 11 families were present and their distribution mainly controlled by channel morphology and sediment character. Based on the distribution of these benthic foraminiferal species, two assemblages have been identified. First assemblage, observed within the Hooghly and Muri Ganga channel, where salinity is comparatively low and sediment is mainly dominated by silt and clay. The most dominating benthic foraminifers of this assemblage are Ammobaculites agglutinans, Cribrostomoides jeffreysii and Asterorotalia trispinosa. Whereas, second assemblage mainly comprise of A. trispinosa, Ammonia beccarii, Asterorotalia spp., Elphidium excavatum, Elphidium crispum and Ammonia tepida noticed over the sand bars and adjoining shallow area. Keywords: channel morphology, Muri Ganga, Hooghly, sand bar